Increasing the Enthusiasm and Participation of 6 Grade Students of SD Negeri Ledug Through the Use of the kahoot in Science Learning - Yusuf Yuniar Ratus; Subuh Anggoro (UM Purwokerto Press, 2025)
This study aims to describe how Kahoot can enhance the enthusiasm and participation of sixth-grade students at SD Negeri Ledug during science learning. Employing a qualitative research method, data were collected through interviews and observations. The analysis involved processing the data to uncover patterns and insights related to student engagement. The results reveal that using Kahoot in science learning significantly increases students' enthusiasm and active involvement in completing assessments. The gamified learning platform creates an interactive and enjoyable environment that motivates students to participate more actively in classroom activities. Observations showed that students were more focused, engaged, and eager to answer questions during lessons involving Kahoot compared to traditional teaching methods. Additionally, interviews highlighted the positive perception of students toward Kahoot, emphasizing its role in making learning fun and reducing anxiety during assessments. The competitive elements of Kahoot encouraged students to stay attentive and perform better while fostering a collaborative atmosphere among peers. In conclusion, this study demonstrates that integrating Kahoot into educational practices not only boosts student participation but also enhances their overall enthusiasm for learning. These findings suggest that Kahoot in science learning can be a valuable tool for educators seeking to improve student enthusiasm, participation and create a more dynamic learning experience.